The Efficiency of Financial Decisions on Stock Returns Moderated Financial Performance - Ainun Jariah; Ninik Lukiana; Hartono Hartono; Jesi Irwanto (Jurnal Ilmu Manajemen Advantage, 2022)
The formation of a company has several objectives, including achieving maximum profit, prospering the owner of the company, and maximizing the value of the company as reflected in its share price. The financial decisions, such as the investment decisions, the funding, and the dividend policy must be considered by the financial managers in order to increase the value of the company. The financial decisions will have an impact on the assessment of the financial performance. The stock returns will be influenced by the financial performance. This study aimed to analyze and acquire the empirical evidences of the effect of the financial decisions on the financial performance and the stock returns, as well as the fact that the financial performance moderates the financial decisions on the stock returns. Based on the Moderated Regression Analysis, the results showed that the financial decisions and the financial performance had no effect on the stock returns. On the other hand, the investment and the funding decisions affected the financial performance. The financial performance could not moderate financial decisions on the stock returns. The limitation of this research is that it only used the financial decision variables and the financial performance in predicting the stock returns.